2018
DOI: 10.1002/mnfr.201700916
|View full text |Cite
|
Sign up to set email alerts
|

Isothiocyanates and Xenobiotic Detoxification

Abstract: The potential of isothiocyanates to antagonize the carcinogenicity of structurally diverse chemicals has been established in animals. A feasible mechanism of action involves protecting DNA by reducing the availability of the genotoxic metabolites of chemical carcinogens by either inhibiting their generation and/or stimulating their detoxification. In vivo as well as in vitro studies conducted in rat/human primary hepatocytes and precision-cut tissue slices have revealed that isothiocyanates can impair cytochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 83 publications
(152 reference statements)
0
15
0
Order By: Relevance
“…Numerous results from cellular and animal models suggest that SFN possesses potent anticancer activity by directly targeting several molecular mechanisms . The most sensitive target for SFN is the Keap‐1‐ and Nrf‐2‐dependent adaptive stress response system.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous results from cellular and animal models suggest that SFN possesses potent anticancer activity by directly targeting several molecular mechanisms . The most sensitive target for SFN is the Keap‐1‐ and Nrf‐2‐dependent adaptive stress response system.…”
Section: Discussionmentioning
confidence: 99%
“…Extensive experimental studies have established that isothiocyanates, both aliphatic and aromatic, such as sulforaphane, erucin, and phenethyl isothiocyanate, owe their potent cancer chemopreventive activity to the fact that they act through a number of mechanisms, modulating favorably the initiation and promotion stages of carcinogenesis [18,22,23,24,25,26,27,28,29,30]. Raphasatin, present in substantial amounts in Daikon (Japanese white radish) as the glucosinolate glucoraphasatin, is consumed extensively in Japan [31].…”
Section: Discussionmentioning
confidence: 99%
“…Many methods have been developed to evaluate the potential of chemical agents to stimulate apoptosis, including morphological studies, biochemical assays, ELISA, flow cytometry analysis and others, of which morphological studies appear to be the most reliable [17]. As previous studies have demonstrated that isothiocyanates manifest their chemopreventive activity, at least partly, by modulating favorably the processes of apoptosis and cell proliferation [18,19,20,21], the present study was undertaken to establish the potential of GRH and its degradation product raphasatin, to initiate apoptosis and cell cycle arrest in human breast adenocarcinoma (MCF-7) cells.…”
Section: Introductionmentioning
confidence: 99%
“…There is a plethora of research to suggest the detoxification and cancer preventative qualities of cruciferous vegetable intake [122,123], especially for cancers related to the gastrointestinal tract [124]. Studies [125,126] have shown that administration of cruciferous-derived compounds, such as sulforaphane, may increase glutathione, glutathione-related enzymes, and even endogenous antioxidant enzymes and inflammatory markers, although results are not always consistent [115]. These compounds may be especially important for individuals with GST polymorphisms.…”
Section: Other Nutrientsmentioning
confidence: 99%